1995
DOI: 10.1136/hrt.74.4.358
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine echocardiography and thallium-201 imaging predict functional improvement after revascularisation in severe ischaemic left ventricular dysfunction.

Abstract: Objectives-To evaluate the concordance between thallium-201 uptake and echocardiographic wall thickening, which are both indicators of potentially reversible myocardial dysfunction, in patients with chronic ischaemic left ventricular failure and to assess their relative contribution to predicting improvement in regional function after revascularisation in a subgroup. Patients and methods-45 patients with chronic ischaemic left ventricular dysfunction (mean (SD) ejection fraction 25 (8)%) underwent echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…6 7 15 Dobutamine is a synthetic β 1 agonist with additional α 1 and β 2 stimulating properties 16. At low dose it detects contractile reserve in dysfunctional myocardium by recruiting contractile proteins.…”
Section: Discussionmentioning
confidence: 99%
“…6 7 15 Dobutamine is a synthetic β 1 agonist with additional α 1 and β 2 stimulating properties 16. At low dose it detects contractile reserve in dysfunctional myocardium by recruiting contractile proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Separate day rest 201 Tl imaging was performed within five days of the exercise imaging. To avoid the difficulties of inadequate redistribution, 201 Tl was injected 10 minutes after sublingual nitroglycerine (0.5 mg), and imaging was performed 60 minutes later 10. Correct angulation was obtained for each image, and the position of the patient was strictly controlled.…”
Section: Methodsmentioning
confidence: 99%
“…[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] The lower specificity of nuclear imaging can again be an issue of duration of follow-up. Recent data have demonstrated that a substantial percentage of segments need longer time after revascularisation to (fully) recover in function.…”
Section: Figmentioning
confidence: 99%